Revolution with a human face: politics, culture, and community in Czechoslovakia, 1989 - 1992 - Krapfl, James (Cornell University Press, 2013)
Revolution with a Human Face -- Contents -- List of Figures, Maps, and Tables -- Acknowledgments -- List of Abbreviations -- Introduction -- 1. The Rhetoric of Revolution -- 2. The Big Bang of the Signifiers -- 3. The Ideals of November -- 4. The Boundaries of Community -- 5. Power in the Streets -- 6. The Will of the People -- Conclusion -- Chronology -- Bibliography -- Index.